Pinenanas Enterprise / Fauzie Matjudin... [et al.] - Matjudin, Fauzie; Ariffin, Mohd Azrin; Halim, Nur Fadilla (2011)
PINENANAS ENTERPRISE is a business that focuses on producing fresh pineapple from the varieties of Josapine . Pineapple (Ananas comosus) a type of tropical plant believed to originate from East Area of South America. Introduced in Malaya in the 16th century by the Portuguese. With rubber crop development, in year 1921 pineapple began to be planted in Singapore, Johor and Selangor as cash crop. Pineapple plantation continued to expand in peat soil area especially in Johor. The pineapple is the leading edible member of the family Bromeliaceae which embraces about 2,000 species, mostly epiphytic and many strikingly ornamental. The pineapple plant is a terrestrial herb 2 1/2 to 5 ft (0.75-1.5 m) high with a spread of 3 to 4 ft (.9-1.2 m); a very short, stout stem and a rosette of waxy, strap like leaves, long-pointed, 20 to 72 in (50- 180cm) long; usually needle tipped and generally bearing sharp, up curved spines on the margins. In Malaysia, there still lots of people who doesn’t know about pineapple plantation. Pineapple is one of the most importance commodities that should be given an attention in research and development. Malaysia has an experience in developing the pineapple industry commercializes since thousand years ago and these advantages should be fully utilized to increase the export. Malaysia had all the strength in producing pineapple for fresh market and processing. The existence of huge quality varieties and high value, efficient planting technology and harvesting, high demand of export make Malaysia as one of the main exporter of pineapple in world.